Lifeworlds of Natural Farmers in Japan - Shoma, Tsuchiya (Jurnal Pemikiran Sosiologi, 2024)
Alternative agriculture should not be narrowly defined as a chemical-free farming system that simply excludes prohibited inputs. Rather, it represents a comprehensive philosophical and ideological framework incorporating political and social dimensions. Both alternative and conventional agriculture are rooted in ideological orientations that reflect agriculture’s societal role. However, the farmers’ motivations for adopting specific practices extend beyond social or ideological factors. An examination of individual farmers’ lives and worldviews reveals that the meaning they derive from agricultural practices often transcends socioeconomic considerations. This paper employs Schutz's concept of the 'Lifeworld' to examine the underlying motivations and practices of natural farming. This study conducted interviews with five natural farming practitioners. First, it elucidated their perceptions of the reasons why agricultural practitioners refrain from using fertilizers. Subsequently, it revealed observational records of their off-farm activities and living environments to examine their relevance to agricultural practices. The results revealed that farmers adopt natural farming according to their lifeworlds, which are based on supra-scientific thought systems such as religion and spiritual cosmologies; that lifeworld dynamically coexists with the modern world within agricultural contexts; and that living spaces and off-farm leisure activities provide insights into the construction and expression of farmers' lifeworlds. In conclusion, analysing farmers' practices through their lifeworlds offers an approach to aligning their self-identity and self-realization with agricultural practices or rural lifestyles in modernised societies.